Media Berperspektif Gender: Faktor yang Mempengaruhi Narasi Keberpihakan pada Korban Kekerasan Seksual di Media Online Tirto.id - Sarjoko Sarjoko; Dewi Sinta Nuriyah (Kalijaga Journal of Communication, 2021)
Tirto.id brings a new color in covering cases of sexual violence in the Indonesian media. This media does something very fundamental in reporting cases of sexual violence, namely siding with the victim. The narrative does not present itself. This research confirms that Tirto.id builds the narrative of partiality at the micro, meso, and macro levels. This research uses a qualitative approach which is analyzed using a descriptive approach. Researchers collected data by digital observation and interviewed two key figures in the coverage of sexual violence on Tirto.id in 2017-2019. Using the theory of Shoemaker and Reese's hierarchy of influences, this article explains how the influence of gatekeepers at five levels makes Tirto.id a medium that can be referred to in reporting cases of sexual violence. This media does not only report cases, but further seeks to encourage the birth of a policy to prevent and handle cases of sexual violence.